Artificial intelligence in the management of public investment projects of the Ministry of Housing, Construction and Sanitation - Álvarez Ochoa, Johnny Óscar (2022)
The research aims to determine that artificial intelligence is related to the management of public investment projects in Peru. This is demonstrated thanks to the study consisting of a literature review and the design of a survey, with a census sample. According to the results of the Spearman test, the described hypotheses are proved and as a contribution, an optimization model for project prioritization (MOPP) is proposed.